Interação genótipo do feijão (Phaseolus vulgaris L.) x produto fermentado no controle da antracnose (Colletotrichum lindemuthianum) - Ribeiro, Luciane Soares (2012)
Currently, the use of alternative products in disease control is a promising field mainly when associated with low cost technologies. This work comprises experiments designed to evaluate the reaction of common bean (Phaseolus vulgaris L.) seedlings under Biochemical Oxygen Demand (BOD) incubator conditions and the reaction of adult plants under field conditions to anthracnose (Colletotrichum lindemuthianum), when subjected to fermentation products treatment. At BOD were tested the effects of the fermented products vinegar, white wine and beer in concentrations of 0, 0.1, 1 and 10%, using the cultivars Carioca and BR-1 Ipagro Macanudo, according to the methodology described for the use of BOD incubator for anthracnose research. Fermented products were evaluated as anthracnose resistance inductors in seeds and seedlings, as well as a curative treatment for seedlings. Results obtained from BOD, revealed that only vinegar showed a linear significant response for concentrations tested and only for the experiment of induced resistance in seedlings. For field experiments, which followed those conducted under BOD conditions, it has been used five research-derived genotypes (TB 02-02, BRS Expedito, TB 98-20, BR IPAGRO 1 - Macanudo and TB 02-21) and five landrace genotypes (Guabiju, TB 02-26, 02-23, TB 02-25 and Amarelinho Iolanda) at the same vinegar concentrations for the BOD experiment, verifying the action of vinegar as anthracnose resistance induction agent. Regarding the field experiment, there were no interactions between vinegar and bean genotypes. There was no effect of inoculation with anthracnose, resulting in a similarity of response between control and inoculated plots. Significant vinegar concentration effects for number of plants per plot and grain yield were detected, with a cubic response, being negative the effects on grain yield. The observed trend for low anthracnose incidence on leaves and pods displayed by more susceptible genotypes when treated with vinegar at the higher concentration, may suggest that the vinegar treatment for susceptible cultivars under high anthracnose incidence might display more pronounced effects. The genotypes showed significant differences for all variables suggested by their distinct phenotypic characteristics, the availability of different market alternatives to farmers producing beans.